Macierzyństwo po rozwodzie. Szanse i zagrożenia - Piotrowska, Maja (Kultura-Społeczeństwo-Edukacja, 2014)
Results of social change which can be seen in the area of family life, especially include crisis of the institution of marriage, redefinition of parent's roles in the parenthood or monoparenthood. The role of the mother is socially important and appreciated. In the academic discourse on the contemporary motherhood, a category of single mother or independent mother appears increasingly. Monoparental family, like the ones in which the spouses got divorced, are becoming more visible form of the family life in the contemporary societies. The article discusses the issue of different faces of motherhood, especially lonely motherhood after the divorce when the family structure is completely changed.